2014
DOI: 10.3389/fpls.2014.00141
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Band-7 family proteins: scaffolds for respiratory chain assembly?

Abstract: The band-7 protein family comprises a diverse set of membrane-bound proteins characterized by the presence of a conserved domain. The exact function of this band-7 domain remains elusive, but examples from animal and bacterial stomatin-type proteins demonstrate binding to lipids and the ability to assemble into membrane-bound oligomers that form putative scaffolds. Some members, such as prohibitins (PHB) and human stomatin-like protein 2 (HsSLP2), localize to the mitochondrial inner membrane where they functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…SLPs can bind cardiolipin and interact with prohibitins ( Mitsopoulos et al , 2015 ). Similar interactions have also been reported for the mitochondria of plants ( Gehl et al , 2014 ; Gehl and Sweetlove, 2014 ). Knock-out mutants for slp1 have reduced complex I levels and activity, and form lower amounts of supercomplexes, indicating that SLPs and prohibitins can affect the assembly and/or the stability of OXPHOS complexes ( Gehl et al , 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…SLPs can bind cardiolipin and interact with prohibitins ( Mitsopoulos et al , 2015 ). Similar interactions have also been reported for the mitochondria of plants ( Gehl et al , 2014 ; Gehl and Sweetlove, 2014 ). Knock-out mutants for slp1 have reduced complex I levels and activity, and form lower amounts of supercomplexes, indicating that SLPs and prohibitins can affect the assembly and/or the stability of OXPHOS complexes ( Gehl et al , 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…The essential role of PHB3 in root development and the cell cycle prompted us to further explore the potential mechanism of its action. The previous data showed that the functions of prohibitin proteins are conserved (Snedden and Fromm, 1997;Ahn et al, 2006;Van Aken et al, 2007;Gehl and Sweetlove, 2014), and the homo PHB1, which is the closest homology of PHB3 in Arabidopsis, is involved in modulating the cell cycle via physically interacting with MCM complex members MCM2, MCM5, and MCM7 in vitro (Rizwani et al, 2009). Intriguingly, MCM2 has been reported to play an essential role on embryo and root meristem development, because disruption of MCM2 is lethal at the very early embryogenesis stage and its over-expression results in reduced root growth (Ni et al, 2009), implying a possible role of MCM2 in modulating primary root development in the phb3 mutant.…”
Section: Phb3 Regulates Cell Proliferation Through Mcm2mentioning
confidence: 99%
“…On the other hand, WP_000755956.1 has been predicted to belong to the band-7 protein family that comprises of a diverse set of membrane-bound proteins characterized by the presence of a conserved domain [72]. The exact function of this domain is not known, but concurrent reports from animal and bacterial stomatin-type proteins demonstrate the ability of binding to lipids and in the assembly of membrane-bound oligomers that form putative scaffolds [73]. We have also predicted WP_001269672.1 and WP_000749269.1 as the lipid binding domain called lipopolysaccharide (LPS)-assembly lipoprotein LptE and the YceI-like domain respectively.…”
Section: Resultsmentioning
confidence: 99%